The Effect of Oyster Mushrooms Flour Substitution to The Acceptance and Nutrient Content of Dried Noodles - Rahmawati Rahmawati; Fitri Wahyuni; Niken Widyastuti Hariati (Jurnal Dunia Gizi, 2018)
Noodle product is a practical food, easy to process, and can be quickly served compared to rice, a type of noodle product that can compete in the market is dried noodles. One of the local foods that can be used as an addition in the manufacture of dried noodles is oyster mushrooms, besides having a good taste also has a high nutritional content such as protein, fiber and iron, but low in carbohydrates, fats and calories. Objectives; The purpose of this research was to determine the acceptability and nutrient content of dried noodles with subsititution of oyster mushroom flour. Material and Method; Randomized Block Design (RBD) was used in this experiment with six levels of treatment with a mixture of flour formula: oyster mushroom flour (in percent), namely: F1 (100: 0), F2 (90:10), F3 (80:20), F4 (70:30), F5 (60:40), F6 (50:50). The acceptability rated from organoleptic conducted on semi trained panelists were as many as 30 students and the levels of nutrtent content from the results of the laboratory test used the test proximat and spectrophotometry. Results; Based on organoleptic and results weighting values, the formula 4 had received higher panelists from other formula with a score of 60.3. Laboratory result showed protein 15.04 g, fat 7.27 g, 7.70 g water, ash 6.03 g, fiber 37.20 g, carbohydrates 17.54 g, and 0.34 mg of iron. Conclusion; The noodle product with proportion of wheat and oyster mushrooms flour has a good acceptability and higher nutrient content compared to commercial  dried noodles.